A variable order framework for 3D nonlinear analysis of reinforced concrete frames under general loading. (1st September 2021) - Poliotti, Mauro; Bairán, Jesús-Miguel; Möller, Oscar
Highlights: A multi-level scheme for the analysis of reinforced concrete frames is developed. General coupling between all the internal forces can be considered. Sectional models of different order can be used within the same element. Different failure modes such as shear or flexural are accurately predicted. Proposed model is suitable for the nonlinear analysis of full-scale structures. Shear deformations and stirrups stresses could be obtained on each integration point. Abstract: A framework for the analysis of three-dimensional reinforced concrete frame structures, capable of reproducing general failure modes, is presented. A force-based model which guarantees the equilibrium between nodal and sectional forces is enhanced by means of a cross-sectional model. It is capable of capturing the complex coupling between all the internal forces. Consequently, different failure modes can be reproduced such as shear, torsional, flexural or axial failures. Material modeling of concrete is made using a plastic-damage model that incorporates a variable dilatancy parameter. The sectional and constitutive models are implemented in OpenSees . The sectional model can be used at each integration point of the force-based element. Alternatively, it can be used only where high coupling between the internal forces is expected, producing a variable order structural model. The validation shows that the frame element is capable of accurately reproduce beams and columns under monotonic and cyclic loads. The framework presented is a powerful numerical instrument for the analysis, design and assessment of reinforced concrete buildings and bridges.